Racial and Ethnic Representation in Local Government - Jones, Daniel B.; Twinam, Tate; Walsh, Randall; Beach, Brian (American Economic Journal: Economic Policy, 2024)
Does the presence of underrepresented racial/ethnic groups in a legislative body differentially impact outcomes for members of those groups? We study close elections between White and non-White candidates for California city council and the corresponding impact on housing values, a summary statistic for neighborhood investment. We find electing non-White rather than White candidates generates differential home value gains in majority non-White neighborhoods. This result, which is not explained by correlations between candidate race and political affiliation or neighborhood racial composition and income, suggests that increased representation can reduce racial disparities. Our results strengthen with increased city-level segregation and council member pivotality.
Keywords: Non-labor Discrimination, Urban, Rural, Regional, Real Estate, and Transportation Economics: Regional Migration; Political Processes: Rent-seeking, Lobbying, Elections, Legislatures, and Voting Behavior, Economics of Minorities, Races, Indigenous Peoples, and Immigrants; Population; Regional Labor Markets; Economics of Minorities; Neighborhood Characteristics